APPLICABILITY OF INTERNATIONAL BEST PRACTICES IN UZBEK HIGHER EDUCATION TO IMPROVE QUALITY AND COMPETITIVENESS - Lutfullayev, Pulatkhon (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Further reforming the higher education system is one of the hot topics in current political life in Uzbekistan. It is in the threshold of a rapid and long term change and improvement process in order to raise quality. In this regard, the international best practices of quality improvement are seen as a key task and objective before the practitioners and managerial staff. How the best practices can be adopted and applied in practice are still under discussion. Therefore, in this article is discussed the problematic issues of quality improvement in the background of the recent developments and policy reforms in higher education system in Uzbekistan. The major components of quality assurance such as adopting the best practices in teaching, research, managing higher educational institutions, and applicability of strategic management tools are argued. Moreover, the possibility of adopting the best practices in the field of internationalization such as student and teacher exchangeand working in international projects are reviewed. Each discussion is mixed with recommendations of and implications from the author.